Thymoquinone Modulates Local MMP-9, IL-10, and IgG in Sciatic Nerve Crush Injury Animal Model - Valentinus Besin; Abdul Hafid Bajamal; I Ketut Sudiana; Mangestuti Agil; Jusak Nugraha; Mohammad Hasan Machfoed; Paulus Budiono Notopuro; Naesilla Naesilla (The Prodia Education and Research Institute (PERI), 2022)
BACKGROUND: Interleukin (IL)-10 is involved in Wallerian degeneration after peripheral nerve crush injury. Oral thymoquinone was previously observed to decrease local immunoglobulin-G (IgG) in a crush-injured rat model. No study has evaluated the pathway of various thymoquinone dosages on local IgG and IL-10 in this injury.METHODS: This experimental study used 126 Rattus norvegicus Wistar rats that were divided into 18 groups: six groups received a placebo, the other six groups received thymoquinone at 100 mg/kg/day and the last six groups received thymoquinone at 250 mg/kg/day, respectively. Rats were sacrificed at 12, 18, 24, 5x24, 6x24, and 7x24 hours. Matrix metalloproteinase-9 (MMP-9), IL-10, and local IgG levels were assessed by Enzyme-Linked Immunosorbent Assay (ELISA). The nuclear factor KappaB (NF-κB) expressions on Schwann cells were examined by flow cytometry. Path analysis was performed using SmartPLS.RESULTS: The path analysis showed that 100mg/kg/day of thymoquinone significantly decreased NF-κB expression. However, NF-κB did not affect local MMP-9, and MMP-9 had no significant relationship with local IL-10 and IgG. Thymoquinone 250 mg/kg/day also significantly inhibited NF-kB expression, decreased local MMP-9, and, in turn, decreased local IL-10 and IgG.CONCLUSION: Administration of oral thymoquinone 250 mg/kg/day decreases local IgG and IL-10 levels via suppressing NF-κB expression and MMP-9 levels.KEYWORDS: thymoquinone, crush injury, IgG, IL-10, MMP-9, NF-κB